Odpowiedzi

  • Użytkownik Zadane
2010-01-26T15:57:51+01:00
A)x²-x dla x= 7
49-7=42
b)a²-3a+1 dla a= -4
16+12+1=29
c)1+x(x+4) dla x= -11
1+x²+4x
1+121+44=166
d)x-2y dla x=1 i y = -1
1+2=3
e)2x²-y(x+1) dla x= -2 i y= 5
2x²-yx-y
8-10-5=-7
f)(m+1)(n-2) dla m= 2 n= 1
mn-2m+n-2
2-4+1-2=-3
1 3 1
Najlepsza Odpowiedź!
2010-01-26T16:00:11+01:00
A)x²-x dla x= 7
7*7-7= 49-7=42
b)a²-3a+1 dla a= -4
-4*(-4)-3*(-4)+1= 16+12+1=29
c)1+x(x+4) dla x= -11
1+(-11)(-11+4)=1+121-44=122-44=78
d)x-2y dla x=1 i y = -1
-1-2(-1)=-1+2=1
e)2x²-y(x+1) dla x= -2 i y= 5
2*(-2*(-2))-5(-2+1)=2*4+10-5=8+10-5=18-5=13
f)(m+1)(n-2) dla m= 2 n= 1
(2+1)(1-2)=2(1-2)+1(1-2)=2-4+1-2=-3

Pod x wstawiasz daną liczbę jeśli dla x=7 to zamiast x wpisujesz 7 itd.
1 1 1